Studi Komparatif Tafsir Tekstual dan Tafsir Kontekstual dalam Pemahaman Ayat-Ayat Sosial di Era Modern - Raihana Zahra; Muhammad Hafidz Khusnadin; Akhmad Aidil Fitra (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2025)
This study aims to conduct a comparative study between the contextual and traditional interpretation methods in understanding social verses in the modern era. In this context, contextual interpretation is proposed as an alternative that is more responsive to the current social, political, and cultural dynamics. This study will analyze how both methods function in interpreting the texts of the Qur'an, especially in the context of implementing social values ​​that are relevant to the challenges of the modern era. In this context, traditional interpretation often focuses on a literal understanding of the Qur'anic text, which can ignore the socio-historical context and contemporary relevance. In contrast, contextual interpretation, popularized by Abdullah Saeed, emphasizes the importance of understanding the social and cultural background when the verses were revealed and relating them to current conditions. The contextual approach offers flexibility in interpretation, allowing for a more dynamic understanding of Islamic teachings, especially in dealing with modern issues such as gender equality and human rights. This methodology includes four steps: analysis of the initial context of revelation, recognition of the complexity of meaning, understanding meaning as an estimate, and linking interpretation to current socio-political conditions. Thus, contextual interpretation is not only relevant to the past but also provides solutions to social challenges faced by modern society. This article asserts that the contextual approach is more capable of answering contemporary problems compared to traditional interpretation methods which tend to be rigid and limited to historical contexts.